Phosphorus Mobilization in Flooded Riparian Soils From the Lake Champlain Basin, VT, USA - Young, Eric O.; Ross, Donald S. (Frontiers in Environmental Science, 2018)
Riparian soils and sediments have the potential to release bioavailable phosphorus, contributing to water quality degradation. Here, we measured phosphorus (P) release to soil porewater (PW) and overlying floodwater (FW) in 12 riparian buffer and 2 agricultural floodplain soils from northwestern Vermont, USA to evaluate P mobilization risk and determine relationships with soil properties (total P, labile P concentrations, pH, organic matter). Duplicate samples (field-moist) were flooded with distilled water in polyethylene beakers modified for PW sampling. Soluble reactive P (SRP) (PW and FW) and PW ferrous iron (Fe2+) concentrations were measured over a 75-day period in the laboratory. Soluble unreactive P (SUP) in PW was also measured twice. Two samples were also flooded after air-drying soil to determine the influence on SRP release. Results showed that PW-SRP tended to increase over time, whereas FW-SRP tended to decrease. The ratio of PW-SRP on day-75 to initial concentrations ranged from 0.21 to 8.4 (mean = 3.2 ± 2.7), while the ratio for FW-SRP was 0.19 to 1.3 (mean = 0.63 ± 0.39). Mean PW- and FW-SRP ranged from 0.03 to 2.2 mg/L and 0.01 to 0.33 mg/L, respectively. Biochemical reduction occurred in 13/14 soils as indicated by PW-Fe2+, while FW remained oxidized (mean dissolved oxygen on day 75 = 6.8 ± 0.3 mg/L). Soil pH was positively related to mean PW- (R2 = 0.48, P = 0.006) and FW-SRP (R2 = 0.47, P = 0.007), whereas mean PW-SUP was inversely related to pH (R2 = 0.44, P = 0.01). Mean ratio of PW-SRP:FW-SRP was 3.5 ± 1.9 and increased with soil pH (R2 = 0.59, P = 0.001). Modified Morgan extractable P was the best predictor of FW and PW-SRP release. Flooding dry soil decreased FW dissolved oxygen concentrations while increasing PW-Fe2+, PW-SRP, and SRP mobilization to FW relative to a field-moist state. Results indicate that SRP release could pose water quality concerns, however mobilization to overlying water was limited by re-adsorption of released P. Our results highlight the importance of integrating measures of labile soil P with hydrologic flow pathways in models to better predict P transport in riparian landscapes.